2019
DOI: 10.1088/1361-6463/ab5c97
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CoFe dusting layer and annealing on the magnetic properties of sputtered Ta/W/CoFeB/CoFe/MgO layer structures

Abstract: We explored the effect of a CoFe wedge inserted as a dusting layer (0.2 nm-0.4 nm thick) at the CoFeB/MgO interface of a sputtered Ta(2 nm)/W(3 nm)/CoFeB(0.9 nm)/MgO(3 nm)/ Ta(2 nm) film-a typical structure for spinorbit torque devices. Films were annealed at temperatures varying between 300 °C and 400 °C in an argon environment. Ferromagnetic resonance studies and vibrating sample magnetometry measurements were carried out to estimate the effective anisotropy field, the Gilbert damping, the saturation magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Notably, the heterostructures with CoFeB as FM are comparatively more versatile due to the fact that the fabrication of SOT based spintronic devices often necessitates processing at high temperatures ∼300 °C-400 °C. 19,20…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the heterostructures with CoFeB as FM are comparatively more versatile due to the fact that the fabrication of SOT based spintronic devices often necessitates processing at high temperatures ∼300 °C-400 °C. 19,20…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this, spintronic devices must have high thermal endurance and maintain their magnetic properties at high temperatures. 19,20 On the other hand, most of the HMs (Ta, W, etc.) and their alloys are susceptible to interdiffusion during post-thermal annealing (T A ) in the layered stack around 300 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For bottom FeB insertion (figure 5(b)), however, 𝛼 reaches the minimum at 0.4 nm FeB insertion and increases dramatically beyond the measurement range with the FeB thickness in both annealing conditions. For those cases, the resonance is too broadened to be resolved, reflecting a very large damping [21]. It also leads to a huge uncertainty in the resonance field and hence 𝜇 𝐻 determination, as mentioned in the preivous section.…”
Section: Impact Of Feb Insertion Layer On Fl Dampingmentioning
confidence: 99%
“…Other works examined the effect of element (Fe or B) composition in CoFeB layers in MTJ stacks on several parameters, including tunnel magneto-resistance (TMR) [16], PMA [17][18][19], and annealing stability [20]. It has been demonstrated that a thickness gradient in the B content can modify the properties of CoFeB/MgO bilayer system such as damping and anisotropy [21]. PMA of the FL was also reported to be improved with increasing the Fe composition in CoFeB, on which its TMR is almost independent [22].…”
Section: Introductionmentioning
confidence: 99%